Bioenergy carbon emissions footprint considering the biogenic carbon and secondary effects. (14th April 2020) - Fan, Yee Van; Klemeš, Jiří Jaromír; Ko, Chun Han
Summary: The sustainability of bioenergy is varying on a case‐by‐case basis. It considerably depends on the source of biomass, management practices (plantation, harvesting, conversion technologies, supply chain, etc.) as well as the assessment boundary and assumptions. This study summarises the carbon emissions footprint (CF) flow of bioenergy by considering the possible sources and system boundary, particularly on the CF of biogenic carbon and secondary effects. The assessment framework has been applied to a demonstrated case study identifying the upper limits of global warming potential of biogenic carbon emission (GWPbio ) and secondary effects contribution where the bioenergy is still superior to the coal, natural gas and gasoline. The circumstances where the other energy source alternatives could have a lower CF than bioenergy are highlighted. For example, coal and natural gas are the selection (lower CF) if the bioelectricity is subjected to the GWPbio higher than 0.57‐0.74 and 0.18‐0.34. CF of bioheat is higher than the heat generated by natural gas when the GWPbio is more than 0.04‐0.40. Gasoline is the selection when the GWPbio of biofuel is higher than 0.12‐0.42. The validity of carbon neutrality assumption of bioenergy possesses a more decisive role in the overall selection of bioenergy compared to the assessed secondary effects such as soil organic carbon changes. This study emphasises the importance of a rigorous CF accounting for bioenergy to support the equitable decision making. Novelty Statement: The novel contributions of this study are: Summarising of the direct and secondary (soil organic carbon changes ‐ above and belowground, biochar application) effects in accounting the CF for a comprehensive assessment framework. Identifying the CF, integrated with biogenic and non‐biogenic accounting, of bioenergy from energy crops and waste/residual. Comparing the identified CF of bioenergy to the other energy alternatives (fossil‐based). Abstract : Direct and secondary carbon emission flow of bioenergy life cycle. Green arrows represent the biogenic carbon (TBCO2 ). Black arrows represent the fossil‐based GHG flow (TFCO2, TCH4, TN2 O). Brown arrows are the secondary effect (TSGHG), where emission is sequestrated or released due to the changes of soil induced by plantation or application of biochar. The dark blue arrow is the sequestrated carbon through, for example, biochar application. Arrow facing upward represents emission, an arrow pointing downwards to the land or geological represent sequestration. The purple arrow is the additional accounting that considers the avoided emissions (replacement of energy consumption with renewable source). *represent the carbon flow which deserves more attention.